2019
DOI: 10.1007/s40544-019-0286-2
|View full text |Cite
|
Sign up to set email alerts
|

Electro-tribological properties of diamond like carbon coatings

Abstract: Diamond like carbon (DLC) coatings typically present good self-lubricating tribological properties that could be of interest in sliding dielectric contacts in multiple electrical applications. In this work electro-tribological studies have been performed on several DLC coatings against aluminum in different humidity conditions, in which the coefficients of friction (CoFs) and electrical contact resistance (ECR) were continuously monitored. Results show that CoF and ECR data can be linked to the properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Besides, lubricants which mainly include solid lubricants and liquid lubricants are widely used for lubrication. There are many advanced solid lubricants such as molybdenum disulfide (MoS 2 ) film [7], diamond-like coating [8], entangled carbon nanotube (CNT) film [9], and polymer material [10,11]. However, their tribological properties are directly influenced by the friction environment, and they are prone to being a wear-out failure after serving for a long time.…”
Section: Frictionmentioning
confidence: 99%
“…Besides, lubricants which mainly include solid lubricants and liquid lubricants are widely used for lubrication. There are many advanced solid lubricants such as molybdenum disulfide (MoS 2 ) film [7], diamond-like coating [8], entangled carbon nanotube (CNT) film [9], and polymer material [10,11]. However, their tribological properties are directly influenced by the friction environment, and they are prone to being a wear-out failure after serving for a long time.…”
Section: Frictionmentioning
confidence: 99%
“…Therefore, the interface will exhibit complex wear behavior, which requires electrical contact materials to have excellent friction and wear resistance, low contact resistance, and good corrosion resistance. Research has shown that preparing appropriate coatings on the surface of metal materials can significantly improve the electrical contact performance of workpieces, such as carbon based coatings, nitride based coatings, oxide based coatings, etc [6][7][8][9]. Among them, titanium nitride (TiN) coatings are widely used, with advantages such as high hardness, good toughness and chemical stability, as well as strong adhesion to the substrate [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Diamond-like carbon (DLC) films are well known for their superior mechanical properties, chemical inertness, and especially excellent self-lubricating performance [1,2], and they have been widely accepted as one of the most promising self-lubricating protective layers in mechanical systems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recently, it was reported that sufficient hydrogen incorporation can make DLC films capable of achieving near-frictionless sliding state with an extremely low friction coefficient (below 0.01) and negligible wear when rubbed in dry inert atmosphere such as nitrogen, carbon dioxide, and argon [3,[20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%